2007
DOI: 10.1111/j.1526-4610.2007.00648.x
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate in Patients With Episodic Migraine: Reducing the Risk for Chronic Forms of Headache

Abstract: Preventive treatment with topiramate in patients with episodic migraine may reduce the risk of developing chronic forms of headache.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 36 publications
1
45
0
4
Order By: Relevance
“…The study failed to demonstrate that topiramate treatment prevented the transformation of episodic migraine to CDH in contradistinction to clinical observations and a post hoc clinical trial analysis (23). There are several possible explanations for this failure.…”
Section: Discussionmentioning
confidence: 95%
“…The study failed to demonstrate that topiramate treatment prevented the transformation of episodic migraine to CDH in contradistinction to clinical observations and a post hoc clinical trial analysis (23). There are several possible explanations for this failure.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, the number of daily use of acute medication was significantly reduced in the topiramate group versus placebo (p < 0.001) [46]. Because the use of acute medication, as well as the frequency of attacks, is a risk factor for progression [4], the authors concluded that preventive treatment with topiramate in patients with episodic migraine could reduce the risk of developing chronic migraine [46]. However, a multicenter RCT including 159 patients who suffered from migraine with high frequency (9 --14 migraine headache days/month) showed that topiramate 100 mg/day did not decrease significantly the development of chronic daily headache at 6 months compared to placebo, although significantly reducing the frequency of migraine and headache days [47].…”
Section: Pharmacokineticsmentioning
confidence: 88%
“…It emerged that significantly fewer patients who received topiramate reported an increase in headache days/month than patients treated with placebo (p < 0.05). Moreover, the number of daily use of acute medication was significantly reduced in the topiramate group versus placebo (p < 0.001) [46]. Because the use of acute medication, as well as the frequency of attacks, is a risk factor for progression [4], the authors concluded that preventive treatment with topiramate in patients with episodic migraine could reduce the risk of developing chronic migraine [46].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…A pooled analysis performed by Limmroth et al [20] concluded that preventive treatment with topiramate in patients with episodic migraine may reduce the risk of developing chronic forms of headache.…”
Section: Topiramatementioning
confidence: 98%